Clinical impact of histologic subtypes in localized non-anaplastic nephroblastoma treated according to the trial and study SIOP-9/GPOH - Weirich, Angela; Leuschner, I.; Harms, D.; Vujanic, G. M.; Tröger, Jochen; Abel, Ulrich; Graf, N.; Schmidt, D.; Ludwig, R.; Voûte, P. A. (Annals of oncology, 2001)
BACKGROUND: Histologic subtypes of standard histology Wilms' tumor (WT) and the effect of preoperative therapy on their clinical and histologic features, deserve to be analysed in respect to outcome to find an adequate baseline for therapy. PATIENTS AND METHODS: The German Society of Paediatric Oncology & Haematology enrolled patients from January 1989 to March 1994 for therapy according the International Society of Paediatric Oncology trial & study 9. Standardised preoperative therapy with dactinomycin and vincristine for 4-8 weeks was generally applied in patients between 0.5 and 16 years with localized renal tumors and imaging typical for WT. In 99.5% of cases representative material was sent for review to the Kiel Paediatric Tumour Registry. For prospective subtyping of 329 WT (258 after preoperative therapy, 71 with immediate surgery) modified Beckwith & Palmer criteria were used. Reduction in volume measured by imaging prior to chemotherapy and surgery was used to assess response (poor response: reduction < 40%; good response: reduction > or = 40%). RESULTS: There were 39% of patients treated with immediate surgery and 12.4% of patients with preoperative therapy in the age group up to 12 months. The difference in age (P = 0.022) was linked with different amounts of epithelial WT (15.5% vs. 3.1%), median age: 0.58 and 0.93 years. Due to the effect of chemotherapy the amount of other WT changed: stromal 0% to 14%, mixed 45.1% to 29.4%, blastemal 39.4% to 9.3%). After preoperative therapy 37.6% of WT were predominantly regressive, 6.6% completely necrotic. Poor response was frequent in differentiated WT (86% of stromal, 75% of epithelial WT) but none relapsed. In the other WT with viable tumor left after preoperative therapy > 70% had good response, poor response was a risk factor (P = 0.0057). CONCLUSIONS: Subtyping according modified Beckwith & Palmer can be used in WT after preoperative therapy to stratify postoperative therapy in future. A milder therapy could be tested in differentiated WT at low stages and an intensified in the others with viable tumor left and poor response, i.e., mainly blastemal WT.